Perancangan Aplikasi Pendeteksi Kebersihan Air Dalam Tangki Air Menggunakan Smartphone Berbasis IoT - Sany, Nasril; Hanum, Gilang Kartika; Sutrisno, Sigit (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2020)
Android is an operating system that is open source, so that it can be developed by users. The development of android applications on smartphones encourages the creation of a smart house system that is used to control and monitor household appliances such as water tanks. Water tanks necessity that must be met today, the difficulty in controlling water in a water tank obstacle that is currently felt in the community. With the help of current technological advances, IoT can reduce the problems that exist today, only using an Android smartphone and microcontroller. Android smartphone functions to send and receive information signals to and from the microcontroller via the internet network. Information is obtained from the microcontroller in form of a Mini D1 Wemos placed in a water tank. Then the LDR provides the cleanliness of the water level based on the incoming light and the LED signals when the water a high degree of saturation. This application uses Bylink which can monitor the water tank by obtaining notifications from the microcontroller that has been implanted in the water tank. With this, the community can enjoy a healthier life because it can control the cleanliness of the water tank easily and practically.